2021
DOI: 10.17161/kjm.vol1414843
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Suburban Kansan Parents Regarding School-Required Immunizations and the Influences of the Coronavirus Pandemic

Abstract: Introduction. Understanding parental attitudes and adherence of recommended childhood vaccination schedules adopts a new level of importance in the era of the Sars-CoV-2019 (COVID-19) pandemic. With hopes for release of a safe and effective COVID-19 vaccine within the near future, understanding parental perception of vaccines is important to design successful vaccination interventions. Methods. A cross-sectional survey was administered to approximately 900 parents in the state of Kansas in May, 2020. Pearson c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several limitations were reported by the included studies. Methodological issues included (1) being unable to establish a causal relationship due to the cross-sectional study design [21,23,30,33], (2) nonprobabilistic sampling that would limit the generalizability of the findings [16][17][18][20][21][22][25][26][27][28][29][30][31][32][33][34][35], (3) small sample size that would result in limited statistical power [22], (4) limited factors being investigated [16,25,28,35]. Self-reported data by parents/caregivers/guardians might cause recall bias, self-selection bias, and social desirability bias [16,18,22,[26][27][28][29]31], and it might not represent children's willingness [28,29].…”
Section: Limitation Of the Included Studiesmentioning
confidence: 99%
“…Several limitations were reported by the included studies. Methodological issues included (1) being unable to establish a causal relationship due to the cross-sectional study design [21,23,30,33], (2) nonprobabilistic sampling that would limit the generalizability of the findings [16][17][18][20][21][22][25][26][27][28][29][30][31][32][33][34][35], (3) small sample size that would result in limited statistical power [22], (4) limited factors being investigated [16,25,28,35]. Self-reported data by parents/caregivers/guardians might cause recall bias, self-selection bias, and social desirability bias [16,18,22,[26][27][28][29]31], and it might not represent children's willingness [28,29].…”
Section: Limitation Of the Included Studiesmentioning
confidence: 99%
“…One study found that suburban clinics had higher HPV vaccination rates than those in urban areas (Chou et al, 2011 ), while another found suburban areas to have higher rates of HPV vaccination than rural and urban areas (Markovitz et al, 2011 ). COVID-19 vaccine research exploring parents and community type is even more limited (Beatty & Villwock, 2021 ; McElfish et al, 2021 ). There is a need to better understand the role of community type to develop effective interventions.…”
Section: Introductionmentioning
confidence: 99%